Respuestas fotosintéticas del fitoplancton de una zona costera del Golfo de México que recibe descargas térmicas - Martínez-Arroyo, Amparo (1999)
Photosynthetic behavior of phytoplankton was analyzed emphasizing the short-term responses to light and temperature. Samples were obtained in a tropical coastal zone with permanent hot water discharges from a thermoelectric plant. They were collected in five periods between March 1993 and October 1994 in four sites where temperatures ranged from 23 to 36 °C. Field data analysis did not show significative differences between the species composition and relative abundance of communities from different sampling sites. Response to photosynthesis experiments was segregated according 10 the origin of microalgae assemblages and composition of samples. Photosynthesis behavior presented alterations in algae assemblages sampled in the site where hot water is discharged, such as rates reduction, higher light requirements, and lower temperature to achieve photosynthetic production than the other algae communities. Therefore, both structure and function analysis must be integrated in order to understand better the disturbed ecosystems.